Physical, mechanical and microstructural characterization of TiC–ZrN ceramics. Issue 14 (1st October 2020) - Nguyen, Thang Phan; Pazhouhanfar, Yaghoub; Delbari, Seyed Ali; Sabahi Namini, Abbas; Babapoor, Aziz; Mohammadpourderakhshi, Yasaman; Shaddel, Shahrzad; Le, Quyet Van; Shokouhimehr, Mohammadreza; Shahedi Asl, Mehdi
Abstract: This study aims to investigate the impact of zirconium nitride (ZrN) additive on the microstructural features and physical-mechanical characteristics of TiC. For this objective, two different samples, namely monolithic TiC and TiC-5 wt% ZrN, were produced by spark plasma sintering method at 1900 °C for 10 min under 40 MPa. X-ray diffraction, field emission scanning electron microscopy, and thermodynamical evaluations confirmed the formation of a single solid solution of (Ti, Zr)(C, N), along with a carbon-rich secondary phase in the doped ceramic. The monolithic TiC provided a higher relative density (95.5%) than the ZrN-doped sample. The fractographical assessment revealed a change in the fracture mode of TiC from transgranular to intergranular with introducing the ZrN additive. Reinforcing TiC with ZrN resulted in a Vickers hardness of 2640 HV0.1 kg, a flexural strength of 444 MPa, and a thermal conductivity of 14.9 W/mK. Furthermore, the TiC–ZrN sample presented a higher coefficient of friction (0.37 on average) compared to the monolithic TiC (0.34 on average).